Bioinks—materials used in printing cells in designed 3D forms. Issue 8 (28th May 2021) - Tamay, Dilara Goksu; Hasirci, Nesrin
Abstract: Use of materials to activate non-functional or damaged organs and tissues goes back to early ages. The first materials used for this purpose were metals, and in time, novel materials such as ceramics, polymers and composites were introduced to the field to serve in medical applications. In the last decade, the advances in material sciences, cell biology, technology and engineering made 3D printing of living tissues or organ models in the designed structure and geometry possible by using cells alone or together with hydrogels through additive manufacturing. This review aims to give a brief information about the chemical structures and properties of bioink materials and their applications in the production of 3D tissue constructs.